Analisis Laporan Arus Kas Operasi, Investasi, dan Pendanaan pada PT Indofood Sukses Makmur Tbk - Listyawati, Reni; Teguh Erawati; Devina Nur Azizah; Fareliana Hardianti; Cindy Cahyati Boru Panjaitan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The cash flow statement describes the movement of cash entering and leaving a company during a specific period. This report is essential for assessing the firm’s ability to generate cash from its operations, finance investment activities, and fulfill its financing commitments. This research aims to examine the cash flow patterns of PT Indofood Sukses Makmur Tbk during the 2020–2024 period, with emphasis on three primary activities: operating, investing, and financing. A quantitative descriptive method is applied, utilizing data collected from the company’s audited and officially published annual financial reports. The analysis is conducted using the horizontal method to observe changes in cash flows between periods. The results indicate that the company’s operating cash flows remain positive despite fluctuations, investment cash flows vary, reflecting active asset management, and financing cash flows tend to decline due to loan repayments and dividend payments. Overall, PT Indofood Sukses Makmur Tbk is able to maintain liquidity from operations, manage investments flexibly, and needs to evaluate financing cash flows to support long-term growth and financial health. These results emphasize the necessity of managing cash efficiently, implementing suitable investment strategies, and adopting sustainable financing policies to ensure the company’s long-term financial stability